PENGARUH MANAGEMENT CONTROL SYSTEM PACKAGE TERHADAP ORGANIZATIONAL PERFORMANCE PADA RUMAH SAKIT JIWA KOTA PEKANBARU - Kamilah, Faizah; Khairani, Zulia; Soviyanti, Efrita (Komunitas Manajemen Kompetitif, 2025)
This research aims to analyze the influence of the Management Control System Package (personal control, cultural control, action control and result control) on Organizational Performance at Rumah Sakit Jiwa Pekanbaru. The data analysis method used is multiple linear regression, F test and t test are used to analyze the data. Data was obtained through a questionnaire method with a Likert scale. The independent variables in this research are personal control, cultural control, action control and result control. Meanwhile, the dependent variable is organizational performance. Data obtained with the help of SPSS 23 software. Statistical test results show that personal control, cultural control, action control and result control influence organizational performance. Data obtained with the help of SPSS 23 software.